Strategies in Coping with Problems Faced by University Students in Speaking Class Across Different Proficiency Levels - Rania Putri Wahyudi; Aridah; Istanti Hermagustiana; Ventje Kalukar; Maria Teodora Ping (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study aimed to describe the problems faced by university students in English speaking classes across different proficiency levels at one of the universities in East Kalimantan and their strategies to overcome the problems. This research used a quantitative survey method. The data was collected using a questionnaire divided into two sections, speaking problems and strategies, shared using Google Forms. 85 of 100 students answered the questionnaire. The findings revealed that the most prevalent problems were affective-related (68.7%) and linguistic-related (62.0%). Specifically, 83.5% of students reported fear of making mistakes, 82.4% struggled with overuse of their mother tongue, and 75.3% faced insufficient grammar knowledge. Beginner students exhibited the highest frequency of issues, with 100% acknowledging fear of mistakes, while intermediate and advanced students also reported significant affective and linguistic challenges, albeit at slightly lower rates (e.g., 86% and 74% for fear of mistakes, respectively). Coping strategies varied by proficiency level: beginners relied heavily on passive methods like watching movies (75%), while intermediate students incorporated more interactive strategies, such as peer practice (37.9%). Advanced learners demonstrated balanced strategies, including regular speaking practice (52.2%) and peer interaction (60.9%). The study results underline the need for tailored pedagogical interventions to support students’ emotional readiness and language competence, emphasizing the importance of strategic practice environments and personalized feedback.